2014
DOI: 10.1371/journal.pone.0089879
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Vital Signs Monitoring and its Association with Mortality among Adults with Severe Sepsis Admitted to a General Medical Ward in Uganda

Abstract: IntroductionOptimal vital signs monitoring of patients with severe sepsis in resource-limited settings may improve outcomes. The objective of this study was to determine the frequency of vital signs monitoring of patients with severe sepsis and its association with mortality in a regional referral hospital in Uganda.MethodsWe reviewed medical records of patients admitted to Mbarara Regional Referral Hospital in Southwestern Uganda with severe sepsis defined by the presence of infection plus ≥2 of the systemic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 22 publications
1
22
1
Order By: Relevance
“…This level of monitoring is generally not possible in resource-limited environments where patients are likely to have vital signs assessed only once per day. 33 However, even a single deranged vital sign value signalled clinical deterioration in an ICU in Tanzania and increasing numbers of deranged values increased the odds of mortality. 30 A subsequent treatment algorithm based on abnormal vital signs improved targeted clinical responses and mortality outcomes for hypotensive patients.…”
Section: Discussionmentioning
confidence: 99%
“…This level of monitoring is generally not possible in resource-limited environments where patients are likely to have vital signs assessed only once per day. 33 However, even a single deranged vital sign value signalled clinical deterioration in an ICU in Tanzania and increasing numbers of deranged values increased the odds of mortality. 30 A subsequent treatment algorithm based on abnormal vital signs improved targeted clinical responses and mortality outcomes for hypotensive patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, implementation would likely be challenging due to critical shortages of both health care workers and material resources in sub-Saharan African healthcare settings [ 36 ] and this tool has not yet been used to direct patient care in clinical trials. For example, a retrospective cohort study in Uganda demonstrated that the median monitoring frequency was 1.1/day for blood pressure and 0.5/day for respiratory rate in patients admitted to medical wards [ 37 ]. For an effective rapid response system, the afferent recognition limb must trigger an efferent ‘action’ limb to manage the at-risk patients [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, no consistent guideline exists for how often to measure vitals. For patients in a hospital environment, the World Health Organization (WHO) recommends temperature measurements every six hours after admission for sepsis, and one to three times daily after the first 24 hours [20]. Since a fever can take up to 60 minutes to develop, failing to probe this often could lead to a delayed detection of sepsis [21].…”
Section: Patient Involvement and Compliancementioning
confidence: 99%